(7x^2-2x+16)+(6x^2+8x-46)

This faces simplification or other simple results.


Step by step Solution

*

Step 1 :

Equation at the finish of step 1 : (((7•(x2))-2x)+16)+(((2•3x2)+8x)-46)

action 2 :

Equation at the end of action 2 : ((7x2 - 2x) + 16) + (6x2 + 8x - 46)

Step 3 :

Trying to factor by splitting the center term3.1Factoring 13x2+6x-30 The very first term is, 13x2 the coefficient is 13.The middle term is, +6x its coefficient is 6.The critical term, "the constant", is -30Step-1 : main point the coefficient of the very first term by the continuous 13•-30=-390Step-2 : discover two determinants of -390 whose sum equals the coefficient that the middle term, which is 6.

-390+1=-389
-195+2=-193
-130+3=-127
-78+5=-73
-65+6=-59
-39+10=-29
-30+13=-17
-26+15=-11
-15+26=11
-13+30=17
-10+39=29
-6+65=59
-5+78=73
-3+130=127
-2+195=193
-1+390=389

Observation : No two such factors can be discovered !! Conclusion : Trinomial deserve to not be factored